RESILIENSI ANAK JALANAN YANG BERSEKOLAH DI RUMAH SINGGAH DIPONEGORO SURABAYA - Sakwa, (Mediakita, 2020)
This study aims to describe the causes of decreased resilience of street kids and also to describe the factors that make children classified as having resilience or not. The approach used in this research is a qualitative approach with a case study design. The subjects in this study were street kids who to school at the Diponegoro Halfway House. Collecting data using interviews, observation, and documentation. From the results of the research conducted, it was found that the resilience of the four research subjects. Subjects had the ability of seven aspects of resilience with different strengths. Economic conditions and parental affection are several reasons why children take to the streets. At their age, who should be used to study in school, it is still a big task for educators. Not all street children who go to school have good resilience abilities, as the results of this study. The results showed that in general the street kids at Diponegoro Halfway House had good abilities and there was one subject who was not resilient. The different in strength is due to family background, the origin, of the child taking to different paths and associations at school.